ANALISIS DAN PENENTUAN STRATEGI PERBAIKAN NILAI TAMBAH PADA RANTAI PASOK KELAPA SAWIT (STUDI KASUS PROVINSI RIAU) - Petir Papilo; Diki Prasetiyo; Misra Hartati; Ekie Gilang Permata; Afdhol Rinaldi (Jurnal Teknologi Industri Pertanian, 2020)
Palm oil has become a leading commodity for improving the economy in Indonesia. At present, many people depend their lives on the plantation and oil palm agro-industry sectors through the establishment of supply chain links. In the palm oil supply chain, there are business actors from upstream to downstream. However, nowaday, every actor has different added values ​​for each level. This study aimed to measure the level of added value at each level of the palm oil supply chain and at the same time determine the strategy of added value improvement in the future. Based on calculations made by the Hayami method, added values at the level of independent smallholders, traders, and factories were 18.6%, 20%, and 28%, respectively. While the profits obtained by farmers, traders, and factories were Rp 4,125,900, Rp 56,400,000, and Rp 4,127,324,500, respectively. Then, by using the Non-numerical Multi Expert Multi Criteria Decision Making Method, recommended strategies have been obtained, among others through improving GAP, and development of cooperation and partnerships. Keywords: added value, palm oil, supply chain, strategy